Pengaruh Sistem Informasi Sumber Daya Manusia dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Beton Elemen Persada - Hani Fitria Rahmani (JURNAL EKONOMI PERJUANGAN, 2019)
A manufacturing company is a company that produces itself, which is then finished with goods which are then sold. The purpose of this study is to find out whether the information system of human resources and work discipline influences the performance of employees at PT Beton Elemen Persada. The method used in this research is descriptive and associative methods. Supported by related theories to draw conclusions that apply in general with a population of 71 people and then proceed with path analysis / path analysis. The results of this study show a significant effect between human resource information systems (X1) and work discipline (X2) on the performance of employees (Y) together (simultaneous) of 73.7%. While the remaining 26.3% was influenced by other things outside the variables examined in this study.